Investigation of the microwave dielectric properties of the Li4x/3Zn2−2xTi1+2x/3O4 system by P–V–L theory and vibration spectroscopy. Issue 24 (15th December 2021) - Cheng, Zelai; Gan, Lin; Chu, Xin; Wang, Dawei; Qi, Zemin; Jiang, Juan; Zhang, Tianjin
Abstract: Li4x/3 Zn2–2x Ti1+2x/3 O4 microwave dielectric ceramics with a spinel phase were prepared via a high-temperature solid-phase method. P–V–L theory, vibration spectra, and XPS were utilized to establish the links between the intrinsic and extrinsic factors and the microwave dielectric properties. According to the characterization, the change in permittivity ( ε r ) was ascribed to the increase in the average bond ionicity of Ti–O( Af iTi-O ) and the polar mode of the lattice vibration; the change in quality factor( Q × f ) resulted from the change in the Ti–O lattice energy ( AU Ti-O ) and existence of oxygen vacancy; the increase in temperature coefficient of the resonance frequency ( τ f ) was triggered by the increase in the Ti–O bond energy. The Li0.6 Zn1.1 Ti1.3 O4 ceramics (x = 0.45) sintered at 1125 °C finally obtained optimal microwave dielectric constants of ε r  = 17.3, Q × f  = 76, 318 GHz and τ f  = -58 ppm/°C.